3 - Women and Development in Urban Senegal: Microcredit and Social Capital - Safiétou Kane, (African Sociological Review, 2014)
The challenging living conditions of many Senegalese families, and the absence of a providing spouse, have led women to covet new economic opportunities, such as microcredit loans. Microcredit loans offer Senegalese women the possibility to financially support their households and become active participants in their economies. The study takes place in Grand-Yoff, an overpopulated peri-urban area of the Senegalese capital city Dakar, where most people face daily survival needs. This research examines the relationships between microcredit activities and the social capital of Senegalese female loan recipients. The study finds that the impact and success of microcredit are intimately tied to the female borrowers’ social capital. Household members, kin groups, communities, social and business networks, formal education, training, professional and business experience are all important sources of social capital for female borrowers. Sources of social capital for the participants in the study can be dependable and enriching, but in many cases reveal themselves to be treacherous, jeopardizing the survival of their households and businesses. The study shows that a providing spouse, formal education, training, business experience, and belonging to social and business networks facilitate women’s success in their microcredit and entrepreneurial activities. It is recommended that microcredit services and programs in Senegal offer their female clients assistance and additional basic services.